The clinical features and diagnosis of Metachromatic leukodystrophy: A case series of Iranian Pediatric patients - JABBEDARI, Sayena; RAHIMIAN, Elham; JAFARI, Narjes; SANII, Sara; NEJAD BIGLARI, Habibe; KHAYATZADEH KAKHKI, Simin (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Jabbehdari S, Rahimian E, Jafari N, Sanii S, Khayatzadeh Kakhki S, Nejad Biglari H. The Clinical Features and Diagnosis of Metachromatic Leukodystrophy: A Case Series of Iranian Pediatric Patients. Iran J Child Neurol. Summer 2015;9(3):57-61. Abstract Objective Metachromatic leukodystrophy disorder (MLD) is one of the rare neurometabolic diseases caused due to lack of saposin B and arylsulfatase A enzyme deficiency. Materials & Methods Eighteen patients diagnosed as metachromatic leukodystrophy in the Neurology Department of Mofid Children’s Hospital in Tehran, Iran between 2010 and 2014 were included in our study. The disorder was confirmed by clinical, EMG-NCV, arylsulfatase A enzyme checking and neuroimaging findings along with neurometabolic and genetic assessment from reference laboratory in Iran. We assessed age, gender, past medical history, developmental status, clinical manifestations, and neuroimaging findings of 18 patients with metachromatic leukodystrophy. Results From 18 patients, 80% were offspring from consanguineous marriages. A family history of metachromatic leukodystrophy disease was positive for four patients. Twelve patients had late infantile form of this disorder and six patients had juvenile form. A history of tonic type seizure was positive in 20% of the patients and tonic spasm was confirmed with clinical information. Electromyographgraphy (EMG) in 96% of patients was abnormal with demyelinating sensorimotor neuropathy pattern. MRI in all patients showed the leukodystrophic pattern as arcuate fibers sparing and subcortical rim in white matter and periventricular involvement. Our diagnosis was confirmed by EMG-NCV findings with sensorimotor neuropathy pattern and the assessment of arylsulfatase A enzyme function. Conclusion MLD is an inheritance metabolic disorder, which was confirmed by the assessment of arylsulfatase A enzyme function, peripheral blood leukocyte that assessed in a referral laboratory in Iran.